Pengaruh Strategi Layanan Digital dan Kepuasan Pelanggan dalam Mendorong Loyalitas Nasabah pada Bank BCA - Angellina, Felisia Grace; Felicia, Felicia; Putri, Restu Novrianda; Noviyanti, Indah (ECONOMETRICS:Journal of Sustainable Economics and Management, 2025)
The purpose of this study is to determine the effect of digital services and customer satisfaction on customer loyalty at Bank BCA. This study was conducted using a quantitative method through data collection via surveys from BCA bank users through questionnaires. The choice of the quantitative method is based on its suitability for measuring and analyzing the relationship between variables in the research, namely digital services, customer satisfaction, and customer loyalty. The sampling technique used is purposive sampling, where samples are taken based on certain criteria. The sample for this study consists of 100 respondents. The results of the analysis prove that the digital service strategy (X1) has a positive and significant impact on customer loyalty (Y), with a path coefficient value of 0.463, a T-statistic value of 5.242, and a p-value reaching 0.000. As previously indicated, there is a large T-statistic value of above 1.96 and a low p-value below 0.05. This means that the better the digital service strategy implemented, the more loyal the customers are to the services. Furthermore, the study results prove that the customer satisfaction variable (X2) has a positive and significant impact on customer loyalty (Y), as shown by the path coefficient value of 0.463 and a T-statistic value of 5.402, far exceeding the threshold of 1.96 (for the 5% significance level). The p-value of 0.000 is smaller than the significance level of 0.05, further confirming that the impact is statistically significant